South African Renal Registry Annual Report 2023 - Jardine, Thabiet; Marais, Nicola; Sebastian, Sajith; Chothia, Mogamat-Yazied; Jacobs, Julian C; Davids, M Razeen (African Journal of Nephrology, 2025)
This is the twelfth consecutive annual report of the South African Renal Registry since its re-establishment and launch, beginning with the December 2012 data on kidney replacement therapy (KRT) in South Africa. The December 2023 data presented here show a decrease in the number of patients on treatment compared to 2022, which is likely due to underreporting by treatment centres. There were 627 patients who started KRT in 2023, an incidence of 10.2 per million population (pmp). Most of these patients (69.7%) were treated in private centres. In December 2023, the total number of patients on treatment with chronic dialysis or transplantation stood at 8 881, down from 9 342 in 2022, with an overall prevalence of 145 pmp. The prevalence was 720 pmp in the private healthcare sector. In the public sector, the overall prevalence was 44 pmp, with the Western Cape being the province with the highest public sector prevalence (155 pmp) and Mpumalanga the province with the lowest (3 pmp).